Reliability, Tangible dan Responsiveness dalam Praktik Pelayanan Pendidikan di Madrasah Tsanawiyah: Kajian Mutu di MTs Al-Muhajirin Kendari - Saputra, Yasin (Shautut Tarbiyah-IAIN Kendari, 2025)
One of the problems often faced by education in Indonesia is the low quality of education, which is caused by various factors, including the process of providing education services that are still far from expectations. The quality of education in the education unit is determined by factors of infrastructure, equipment, fun learning methods, the role of the teacher, and the leadership of the madrasah head, so that the quality of service must be a concern in order to satisfy customers. This research uses a qualitative method with a phenomenological study approach, where data is collected through interviews, observations, and documentation. The data analysis technique consists of collection, reduction, presentation, and conclusion drawing, with data validity checking through source triangulation, technical triangulation, and member check. The results showed that the quality of service at MTs Al-Muhajirin still needs improvement in several aspects: 1) reliability, where teacher attendance has taken place but has not been consistent; 2) physical evidence, where facilities such as classrooms and libraries have not been maintained; 3) responsiveness, where teachers' response to students' and parents' needs is quite good.